Evaluating the Quality Status and Sustainability of Anggoeya Spring in the Ecological Dimension using the Rapid Appraisal for Springs Method - Kahirun; Ramadhan, La Ode Ahmad Nur; Erif, La Ode Muhammad; Mubarokah, Umi (Indonesian Journal of Environmental Management and Sustainability, 2025)
Water quality is essential for community needs. This study uses physical, chemical, and biological parameters to evaluate the quality and sustainability of Anggoeya Spring, Kendari City. The Southeast Sulawesi Health Laboratory tests assessed compliance with water quality standards, while pollution levels were analyzed using the Pollution Index. Sustainability was examined through the RAP-SPRINGS method, focusing on ecological aspects. Results showed compliance with most standards, except for BOD, COD, and total coliform levels. Anggoeya Spring was classified as lightly polluted but ecologically sustainable. Key sensitive attributes land cover in the catchment area, land cover within a 200 m radius, catchment area criticality, and water source utilization-highlight the need for targeted conservation and rehabilitation efforts. Therefore, prioritizing land and forest management in the catchment area and surrounding zones is crucial for sustaining Anggoeya Spring. This includes the need for improved raw water treatment, especially water treatment technology, due to the high total coliform content in Anggoeya spring water. This study evaluates water quality, determines pollution levels, and analyzes sustainability using the RAP-SPRINGS method. It emphasizes crucial ecological factors for conservation, advocates land rehabilitation, and highlights the necessity of improved water treatment. Ultimately, it contributes to environmental preservation and sustainable water management.